PostGraduate Prospectus - Kabale University (Kabale University, 2023)
The Directorate of Graduate Training supports our postgraduate community. It provides a University-wide community of peers from all academic disciplines offering networking and social opportunities. The Directorate of Graduate Training is a gateway to advice and support for postgraduates, working with the other University support services to ensure you have access to high-quality training, facilities, tutoring and supervision. You can take part in a busy programme of events throughout the academic year, such as the Annual International Conference, grants writing and communicating with the public in innovative and creative ways. The Directorate of Graduate Training will give you formal and informal opportunities to raise your profile, network with peers and colleagues, apply transferable skills and help you make the most of your time here. As a member of our postgraduate community, you will become one of the exceptional local, national and international students who join us each year. The Directorate of Graduate Training will assist you to be a Thinker, Innovator, Leader and Communicator who is Future-Ready